Implementation of Principal Risk Management in the Development of Changes in Educational Institutions - Andriani, Rini Dewi; Nasir, M.; Ramadhani, Ramadhani; Subban, Subban (Academy of Education Journal, 2024)
This article seeks to find out how the principal implements risk management in developing any changes that occur in an educational institution. In this research, a qualitative approach was used with the key informants in this research being the Principal and Deputy of SMP IT Nurul Ilmi Medan Estate. Meanwhile, the supporting informants in this research were teachers, staff and students of SMP IT Nurul Ilmi Medan Estate. Field data was obtained through observation, interviews and documentation. After collecting data, researchers carried out data analysis. Based on findings in the field, it is revealed that the role of leaders in change management includes creating effective working relationships, shifting manager functions, leading by example, influencing others, developing team work, involving subordinates in decision making, making empowerment of subordinates a way of life; and build commitment. Apart from his big role in bringing about change, a leader must also have a mature strategy to make this change a reality